Information System of Location-Based Advertising Ordering and SMS Targeted (SiPesat) at MDMedia - Utami, Lilyani Asri; Suparni, Suparni; Wulan, Anggraeni (Politeknik Ganesha Medan, 2019)
The LBA (Location Based Advertising) and SMS Targeted ordering system on MDMedia is designed to provide facilities for sales and operations in handling campaign orders. The running process still uses the manual method, that is, the user completes the form and sent it via e-mail to the operation for the verification process. This business process is very ineffective given the large number of LBA and SMS Targeted orders that come every day without recording data campaigns. The system design method uses the waterfall method. Program implementation uses PHP language with a database using MySQL. The development of the LBA and SMS Targeted ordering information system is able to provide effective work, because it can be well organized during the ordering process and report submission.